Yield and agronomic performance response to irrigation on banana cultivars ‘Prata Anã’ and ‘Prata Graúda’ (Revista de Ciências Agroveterinárias, 2015)
An adequate irrigation system with high efficiency application can improve vegetative growth, yields, plant height, pseudostem diameter, leaf area index and number of standing leaves on banana plants. This paper compares responses to the foot-dripping irrigation of two banana cultivars: ‘Prata Anã’ and ‘Prata Graúda’. Yields and agronomic traits related to growth parameters are analyzed. The trial was carried out at Universidade Católica Dom Bosco Experimental Station in Campo Grande, MS, Brazil, between December 2005 and April 2007. Traits related to production cycle were: number of days from planting to flowering and to harvesting as well as from flowering to harvest. The following production traits were evaluated: yields; bunch weight; number of hands per bunch; number of fruits per bunch; average fruit weight, diameter and length. The experimental design was random blocks in factorial scheme 2 x 2 (cultivars x irrigation) with five repetitions and three useful plants per plot. Results showed statistically significant differences between cultivars. There were also significant differences on superior development performance, yield and agronomic traits when cultivars were irrigated. It indicates that the use of strategic technologies, such as irrigation, can enhance banana production in the central part of Mato Grosso do Sul, Brazil.
Keywords: Musa spp.; drip-irrigation; dry season.